CRITICAL THINKING SKILLS PROFILE IN DECISION MAKING ON OPTICAL MATERIALS AT SMA NEGERI 10 SURABAYA - ANDIKA, LOUIS; SETYARSIH, WORO (Inovasi Pendidikan Fisika, 2019)
Abstract Critical thinking skills is the ability to be possessed by every individual in the face of various problems. Differences level thinking skills of each individual affects all aspects of their daily activities, especially related to the concept and materials physics. Manifold ex post facto study aims to describe the profile of the students critical thinking skills to solve the problems of optical devices. Instruments critical thinking is modified from standard instruments critical thinking Watson-Glaser Critical Thinking Appraisal (W-GCTA) and the California Critical Thinking Skills Test (CCTST) on the material of optical devices. The samples were 63 students (2 classes XI MIA) SMA Negeri 10 Surabaya, 10% of the total number of students as many as 261 students. Based on the test of critical thinking skills can be obtained that the average percentage of each indicator critical thinking is inference (23%), assumptions (62%), deduction (72%), interpretation (53%), arguments (54%), analysis ( 34%), evaluation (37%), and the conclusion (26%), as well as an explanation (33%). Each indicator of the level of critical thinking skills profiles majority being down. In an essay about the indicator value is still a small percentage even though other indicators enough and it was very good. Keywords: Critical Thinking Skills Profile, Optical Device Material, Problem Solving